A high school teacher’s rating as a means of increasing the competitiveness of academic staff - Tatyana Nikolaevna Poddubnaya; Anna Andreevna Yurchenko (Вестник Майкопского государственного технологического университета)
In modern conditions the quality of education in higher education is considered in the context of increasing the competitiveness of academic staff. The system of professional education at a university imposes certain requirements on a teacher and the quality of his work, which is the basis for the rating of the activities of academic staff. The research problem is to identify mechanisms for assessing the quality of labor of a university academic staff as a driving force of material incentives. The purpose of the research is to analyze and generalize the experience of developing and implementing a rating assessment of the work of academic staff, which underlies an effective contract. The methods of analysis, synthesis, analogy, generalization have been used. The result of the research is substantiation of the principles for evaluating the effectiveness of the activities of the Kuban State University of Physical Culture, Sports and Tourism academic staff. Key findings: basic criteria and indicators for assessing the effectiveness of the activities of the academic staff have been described, an example of the introduction of an effective contract for the teaching staff at a particular university has been given; a rating assessment of the effectiveness of teachers in a particular university has been considered. The results can be extrapolated to the practice of developing a matrix of performance indicators for teachers of other higher educational institutions.